先化简,再求值:(3a^2-ab)/(9a^2-6ab+b^2),其中2a+b=0
1个回答
(3a^2-ab)/(9a^2-6ab+b^2)
=a(3a-b)/(3a-b)^2
=a/(3a-b)
2a+b=0
则b=-2a
则原式=a/5a=1/5
相关问题
先化简.再求值:(3a^2-ab)/(9a^2-6ab+b^2),其中a=3/4,b=-2/3
先化简,再求值:3a2−ab9a2−6ab+b2,其中a=-8,b=[1/2].
先化简,再求值:(3a²b-ab²)-2(ab²-3a²b),其中a=-2,b=
先化简,再求值:-5(a2-4ab+3)+2(a2-9ab+6.5),其中a=23,b=-6.
先化简,再求值:[ab(a²-3b)+3ab²]*(-2ab²),其中a=-1/2,b=-
先化简,再求值:-(a2-2ab)•9a2-(9ab3+12a4b2)÷3ab,其中a=-1,b=-2.
先化简,再求值:-(a2-2ab)•9a2-(9ab3+12a4b2)÷3ab,其中a=-1,b=-2.
先化简再求值(3a-2b)(3a+2b)+2ab³÷(-ab),其中a=-2,b=-1.
2(a²-2ab-b²)-(-a²+3ab+3b²) 先化简,再求值;其中a是绝
先化简,再求值(9a-12ab+5b)-2(7a-6ab+5b),其中a=1/2,b=-1/2